Using Images in Speech Skills Instruction - Siraj, Muhammad Chobir (Al-Tadris: Jurnal Pendidikan Bahasa Arab, 2017)
Speech was the most important thing in the life of human being and it plays an important role in society and considered one of four the most important skills of Arabic language. Speech is a basic standard to measure students capability in Arabic language instruction. And said who can speech fluently for discribing something that is bugging their thought then they are called success in studying language. Therefore, it is necessary to empower students, especially those who are studying Arabic language in primary stage. After interviewed the teacher and obeserved in the class, researcher noticed that students don’t want to speak Arabic in front of others because they afraid being wrong and feeling difficult in extending the right word, and if they talk with a conversation they spoke fluently. So, the teacher of Arabic language should using media in instruction of speech skills, and the government has to provide various educational media appropriately.